Diagnostic accuracy of high-resolution ultrasonogram compared to magnetic resonance imaging in rotator cuff tears – A prospective comparative study - Jayanth Murugan; A Venkata Sai Kartheek; Raam Mohan Selvarajan; A Vignesh Siva Anand; Sathish Muthu; Madhan Jeyaraman (Apollo Medicine)
Background: One of the most common causes of shoulder pain is a rotator cuff tear. In the absence of surgery, rotator cuff tears can be detected using noninvasive diagnostic modalities such as magnetic resonance imaging (MRI) and ultrasound. High-resolution ultrasound (HRUS) and MRI were used in this study to compare the accuracy of their respective diagnostic methods in the detection of rotator cuff tears. Materials and Methods: MRI shoulder was used in this prospective study, which included patients who had been diagnosed with rotator cuff injuries and had been referred for the procedure. In addition to an MRI of the shoulder, an HRUS was performed. It was determined whether HRUS could reliably detect tears in individual components of the rotator cuff complex and whether it could also detect tears in the rotator cuff complex by comparing the results to those obtained with MRI findings. The diagnostic accuracy of the screening test was evaluated using Kappa statistics, which were combined with 95% confidence intervals to arrive at a conclusion. Results: A total of 90 patients were enrolled, with a mean age of the study population was 40.49 ± 14.69 years. The predictive validity of HRUS rotator cuff tendon tears in predicting MRI tendon tears had a diagnostic accuracy of 68.89%, 98.89%, 88.89%, and 97.78% for supraspinatus, infraspinatus, subscapularis, and teres minor, respectively. Conclusion: Although HRUS is operator dependent, it detects infraspinatus and subscapularis tendon tears with good sensitivity and specificity on par with MRI but not with tears of supraspinatus and teres minor. HRUS is equivalent to MRI in detecting peribicipital fluid, joint effusion, and subacromial impingement. Whereas HRUS did not substantially identify sub-coracoid impingement.